2004
DOI: 10.1516/u8xv-lg0a-wxnw-1285
|View full text |Cite
|
Sign up to set email alerts
|

The shaping of masculinity: Revisioning boys turning away from their mothers to construct male gender identity

Abstract: This paper offers an understanding of the nature of the internalization processes involved in the shaping of male gender identity founded on the boy's unique struggles in separating from his mother. The underpinning for the initial development of a sense of masculinity is reconsidered as the author questions the widely held idea of Greenson and Stoller that a boy normatively has to ‘dis‐identify’ from his mother to create his gender identity. Import rather is placed on the conscious and unconscious aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
0
50
0
3
Order By: Relevance
“…Psychoanalytic literature regards identification with a father as an important aspect of masculine gender identity development [19]. In our study, Benny also wanted to identify with his father by taking his surname, recognizing that this holds some symbolic meaning.…”
Section: Searching For the Absent Biological Fathersmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychoanalytic literature regards identification with a father as an important aspect of masculine gender identity development [19]. In our study, Benny also wanted to identify with his father by taking his surname, recognizing that this holds some symbolic meaning.…”
Section: Searching For the Absent Biological Fathersmentioning
confidence: 99%
“…By taking good care of his baby boy, he seemed to be vicariously fulfilling some of his unmet emotional needs as a boy child [19]. The interview revealed that the birth of his boy child also reactivated some of his unresolved childhood issues with regard to his absent father.…”
Section: Nelson: "Yeah I Did Not Listen To My Friends When They Saidmentioning
confidence: 99%
“…The complexity of this terrain only increases 3 In "Ego and Reality," Loewald (1951) calls into question these kinds of schematic simplifications of the roles of the mother and the father in psychic development. Diamond (2004) offers a more recent analysis of schematic notions about boys and their complex bonds to their mothers.…”
Section: F R E U D ' S P S Yc H Oa N a Ly T I C M O D E O F T H O U Gmentioning
confidence: 99%
“…In contrast, under "good enough" conditions, the boy's turning away from his mother is transitional (Diamond 1998;Fast 1999). This transitional turning away from the mother helps the boy to differentiate and separate from his primary external object.…”
Section: Revisioning Boys Turning Away From Their Mothersmentioning
confidence: 99%
“…These challenges emerge particularly during the oedipal and latency phases, in adolescence and young adulthood, and again in mid-and later life. Though it is beyond my scope here to examine each of these critical junctures, it is pertinent nonetheless to note the main gender identity-related factors operating throughout these other phases (see Freud 1924;Erikson 1963;Blos 1978;Levinson et al 1978;Schalin 1983;Colarusso 1995;Diamond 1998Diamond , 2004a.…”
Section: Transforming Masculinity In the Course Of Male Developmentmentioning
confidence: 99%